Effects of Human RelA Transgene on Murine Macrophage Inflammatory Responses - Stamatia Papoutsopoulou; Lorna Morris; Andrew Bayliff; Thomas Mair; Hazel England; Massimiliano Stagi; François Bergey; Mohammad Tauqeer Alam; Raheleh Sheibani-Tezerji; Philip Rosenstiel; Werner Müller; Vitor A. P. Martins Dos Santos; et al. (Biomedicines, 2022)
The NFκB transcription factors are major regulators of innate immune responses, and NFκB signal pathway dysregulation is linked to inflammatory disease. Here, we utilised bone marrow-derived macrophages from the p65-DsRedxp/IκBα-eGFP transgenic strain to study the functional implication of xenogeneic (human) RelA(p65) protein introduced into the mouse genome. Confocal imaging showed that human RelA is expressed in the cells and can translocate to the nucleus following activation of Toll-like receptor 4. RNA sequencing of lipid A-stimulated macrophages, revealed that human RelA impacts on murine gene transcription, affecting both non-NFκB and NFκB target genes, including immediate-early and late response genes, e.g., Fos and Cxcl10. Validation experiments on NFκB targets revealed markedly reduced mRNA levels, but similar kinetic profiles in transgenic cells compared to wild-type. Enrichment pathway analysis of differentially expressed genes revealed interferon and cytokine signaling were affected. These immune response pathways were also affected in macrophages treated with tumor necrosis factor. Data suggests that the presence of xenogeneic RelA protein likely has inhibitory activity, altering specific transcriptional profiles of key molecules involved in immune responses. It is therefore essential that this information be taken into consideration when designing and interpreting future experiments using this transgenic strain.